2003
DOI: 10.1136/ijgc-00009577-200303000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Is bacterial vaginosis associated with cervical intraepithelial neoplasia?

Abstract: Previous research has produced conflicting results regarding the association of bacterial vaginosis (BV) and cervical intraepithelial neoplasia (CIN). These studies have been weakened in their conclusions mainly by failure to adequately control for the presence of sexually transmitted infections (STIs). One proposed mechanism suggesting that carcinogenic nitrosamines acting either independently or via human papilloma virus (HPV) has not been fully tested previously. We undertook a prospective, case-controlled,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…However, these ambivalent results may be attributed to the different tools used in the diagnosis of BV. Of the above-mentioned studies, two used a BV diagnosis with three other measurements, including pH, clue cells after Gram stain, and a positive amine or whiff test [23,25], and the other used the Nugent scale [24]. Although the correlation between BV and CIN remains to be determined, our results are in support of such a correlation.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, these ambivalent results may be attributed to the different tools used in the diagnosis of BV. Of the above-mentioned studies, two used a BV diagnosis with three other measurements, including pH, clue cells after Gram stain, and a positive amine or whiff test [23,25], and the other used the Nugent scale [24]. Although the correlation between BV and CIN remains to be determined, our results are in support of such a correlation.…”
Section: Discussionsupporting
confidence: 67%
“…To date, several studies have explored the role of BV in cervical neoplasia; they have reported conflicting findings. In one prospective study, the CIN rate and the quantity of nitrosamines produced in women with BV did not differ from those in women with normal flora [23]. Another longitudinal study reported no influence of abnormal flora on the presence of atypical endocervical cells [24].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining the relationship between BV and CIN have produced conflicting results and conclusions. The results ranged from a very strong association between the two conditions such as that found in the study by Platz Christensen et al to there being no association as in the study by Peters et al 19 Our study shows that BV was associated with a significantly increased risk of HPV infection and CIN. However, BV combined with HPV infection does not increase the prevalence of CIN (x 2 = 3.61, P = 0.462).…”
Section: Genital Tract Infections In Beijingsupporting
confidence: 64%
“…One proposed mechanism suggesting that carcinogenic nitrosamines acting either independently or via human papillomavirus (HPV) has not been fully tested previously. Boyle et al 16 undertook a prospective, case-controlled, cross-sectional study where the presence of HPV, which is known to be associated with the development of CIN, was controlled for. Women with BV were not found to have CIN more frequently than women with normal vaginal flora and the quantities of nitrosamines produced by women with BV did not differ significantly from women without BV.…”
Section: Discussionmentioning
confidence: 99%